Neuromuscular Junctions as Key Contributors and Therapeutic Targets in Spinal Muscular Atrophy - Boido, Marina; Vercelli, Alessandro (Frontiers in Neuroanatomy, 2016)
Spinal muscular atrophy (SMA) is a recessive autosomal neuromuscular disease, representing the most common fatal paediatric pathology. Even though, classically and in a simplistic way, it is categorized as a motor neuron (MN) disease, there is an increasing general consensus that its pathogenesis is more complex than expected. In particular, neuromuscular junctions (NMJs) are affected by dramatic alterations, including immaturity, denervation and neurofilament accumulation, associated to impaired synaptic functions: these abnormalities may in turn have a detrimental effect on MN survival. Here we provide a description of NMJ development/maintenance/maturation in physiological and pathological (SMA) conditions, focusing on pivotal molecules and on the time-course of pathological events. Moreover, since NMJs could represent an important target to be exploited for counteracting the pathology progression, we also describe several therapeutic strategies that, directly or indirectly, aim at NMJs.